2022
DOI: 10.3390/jof8050453
|View full text |Cite
|
Sign up to set email alerts
|

Piriformospora indica and Azotobacter chroococcum Consortium Facilitates Higher Acquisition of N, P with Improved Carbon Allocation and Enhanced Plant Growth in Oryza sativa

Abstract: The soil microbiome contributes to nutrient acquisition and plant adaptation to numerous biotic and abiotic stresses. Numerous studies have been conducted over the past decade showing that plants take up nutrients better when associated with fungi and additional beneficial bacteria that promote plant growth, but the mechanisms by which the plant host benefits from this tripartite association are not yet fully understood. In this article, we report on a synergistic interaction between rice (Oryza sativa), Pirif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…According to a study by Abdelaziz et al [15], Arabidopsis seedlings that were inoculated with P. indica demonstrated a noteworthy reduction in Na + uptake and an increase in K + concentration compared to non-inoculated plants. Enhanced nutrient uptake and growth promotion by P. indica colonization was also reported in rice [16]. Drought and salinity stress share common characteristics in terms of their impact on plants.…”
Section: Introductionmentioning
confidence: 67%
“…According to a study by Abdelaziz et al [15], Arabidopsis seedlings that were inoculated with P. indica demonstrated a noteworthy reduction in Na + uptake and an increase in K + concentration compared to non-inoculated plants. Enhanced nutrient uptake and growth promotion by P. indica colonization was also reported in rice [16]. Drought and salinity stress share common characteristics in terms of their impact on plants.…”
Section: Introductionmentioning
confidence: 67%
“…Moreover, Wang H.-R. et al (2022) reported how AMFs were introduced into tobacco plants and further revealed the association between improved N assimilation and upregulation of nitrate reductase (NR) potential. The greater the NR activity granted for a better N uptake, the greater the increase in the production of amino acid and protein biosynthesis (Bandyopadhyay et al, 2022).…”
Section: Promotion Of Nutrient Utilizationmentioning
confidence: 99%
“…It shares similarities with some AM fungi, such as G. mosseae and Gigaspora margarita (Chen et al, 2007 ; Venice et al, 2020 ). They are both endophytic fungi that can coexist with the host plant (Singh et al, 2000 ; Kesharwani et al, 2022 ), promote the absorption of mineral elements and cycling substances in the soil, and enhance the plant's resistance to biotic and abiotic stress (Xu et al, 2018 ; Bandyopadhyay et al, 2022 ). Compared to the AM fungus, P. indica has notable advantages, such as its ability to obtain nutrition from non-living sources and its wide range of host plants (Varma et al, 2001 ; Deshmukh et al, 2006 ; Oelmüller et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%